STUDI GEOLOGI DAERAH TIHENGO DAN SEKITARNYA KECAMATAN PONELO KEPULAUAN KABUPATEN GORONTALO UTARA - Hidayansya, Taufik; Arifin, Yayu Indriati; Akase, Noviar (UNM Geographic Journal, 2024)
The research titled Geology of the Tihengo Area and Surroundings, Ponelo Kepulauan District, North Gorontalo Regency was conducted with the aim of understanding the geomorphological, stratigraphic, and geological structural conditions of the area using geological survey or mapping methods. Based on the research findings, the Tihengo area and its surroundings are located at an elevation of 0-125 meters above sea level, featuring varied morphology ranging from lowlands to steep hills. The region is predominantly comprised of residential, agricultural, and plantation lands, with vegetation generally classified as sparse to moderate. The relief in this area includes plains to steep hills with "V"-shaped valleys, formed due to the influence of both endogenous and exogenous geomorphological processes, including tectonic activity, magmatism, as well as ongoing erosion and sedimentation. Slope analysis shows a range of slopes from flat to very steep, with varying percentages of land area. The geomorphology of this area is divided into three main units: volcanic hill unit, denudational hill unit, and coastal plain unit. The stratigraphy of the research area consists of a sequence of andesite rocks, conglomerates, sandstones (coarse, medium, and fine), as well as coastal alluvial deposits. The geological structure is identified based on lineaments observed on DEMNAS imagery, with a general northeast-southwest orientation